PENGARUH VARIASI KONSENTRASI AMPROTAB SEBAGAI DESINTEGRANT TERHADAP SIFAT FISIK TABLET EKSTRAK BUAH PARE (MOMORDICA CHARANTIA L.) - Sri Rahayu; Nor Anisah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Bitter melon (Momordica charantia L.) is a type of medicinal plant that is widely used by the public. Charantin is one of the nutritious compounds contained in bitter melon. Charantin compounds can be used to reduce glucose levels in the blood so that it is widely used as a diabetes medicine. The research aims to determine the effect of variations in the concentration of amprotab as a desintegrant on the physical properties of Pare (Momordica charantia L.) extract tablets has been conducted. Viscous extract was made by maceration method by using ethanol 96%. Tablets made by wet granulation method in two different desintegrant concentration of 9,6% and 18%. Dried granule tested with flowability, angle of repose and indeks of compressibility. Tablet evaluation includes uniformity of weight test, friability test, hardness test and disintegration test. The results showed that formula with amprotab as desintegration at 9,6 % concentration was able to produce tablets that met the requirements. Variation in concentration of desintegrant material take effect on the uniformity of weight, hardness friability and disintegration time.